The multifunctional solute carrier 3A2 (SLC3A2) confers a poor prognosis in the highly proliferative breast cancer subtypes - El Ansari, Rokaya; Craze, Madeleine L.; Diez-Rodriguez, Maria; Nolan, Christopher C.; Ellis, Ian O.; Rakha, Emad A.; Green, Andrew R. (Cancer Research UK, 2018)
Background: Breast cancer (BC) is a heterogeneous disease characterised by variant biology, metabolic activity and patient outcome. This study aimed to evaluate the biological and prognostic value of the membrane solute carrier, SLC3A2 in BC with emphasis on the intrinsic molecular subtypes.